MENELUSURI KEHENDAK TUHAN MELALUI RAJUTAN BAHASA: STRUKTUR ESTETIKA BAHASA AL-QUR’AN - Rahmatullah, Lutfi (IAIN Kediri, 2015)
This paper aims to explore the significance of Ã¢â‚¬ËœlanguageÃ¢â‚¬â„¢ in shaping human civilization; even God chose Ã¢â‚¬ËœlanguageÃ¢â‚¬â„¢Ã‚Â as a medium of communication with His people. It is undeniable that Ã¢â‚¬ËœArabicÃ¢â‚¬â„¢ language is the language of theal-QurÃ¢â‚¬â„¢an. Departing from this, this paper will study the aesthetic structures of the QurÃ¢â‚¬â„¢anic language becauseÃ‚Â the language contains divine, absolute dimension of culture and humanity. Using a philosophical approach, thisÃ‚Â paper will describe the significance of human language existance, while the structure of the aesthetic languageÃ‚Â of the al-QurÃ¢â‚¬â„¢an.Keywords: Bahasa, Struktur al-QurÃ¢â‚¬â„¢an, Estetika